Chemical analysis of food techniques and applications - Picó, Yolanda (Academic Press, 2012)
Chemical Analysis of Food: Techniques and Applications reviews new technology and challenges in food analysis from multiple perspectives: a review of novel technologies being used in food analysis, an in-depth analysis of several specific approaches, and an examination of the most innovative applications and future trends. The book is structured in two parts: the first describes the role of the latest developments in analytical and bio-analytical techniques and the second reviews the most innovative applications and issues in food analysis. Each chapter is written by experts on the subject and is extensively referenced in order to serve as an effective resource for more detailed information. The techniques discussed range from the non-invasive and non-destructive, such as infrared spectroscopy and ultrasound, to emerging areas such as nanotechnology, biosensors and electronic noses and tongues. Important tools for problem-solving in chemical and biological analysis are discussed in detail. Provides researchers with a single source for up-to-date information in food analysis Single go-to reference for emerging techniques and technologies Over 20 renowned international contributors Broad coverage of many important techniques makes this reference useful for a range of food scientists.
Keywords: Food -- Analysis.; Food -- Composition.; elektronické knihy; electronic books